Studi Model Isoterm Adsorpsi Kristal Violet oleh Biosorben Kulit Ubi Kayu (Manihot esculenta) - Ramadhan, Muhammad Dafin; Iriany; Misran, Erni; Turmuzi , Muhammad (Talenta Publisher (Universitas Sumatera Utara), 2021)
Crystal violet is a dye that has many uses, but its waste can be harmful to humans and the environment. Adsorption is the most useful method for removing crystal violet waste compared to other separation methods because of its efficiency and viability. Cassava peel is a material that has potential to be an adsorbent. Cassava peel is suitable as an adsorbent because of its high cellulose, hemicellulose, and lignin content. In carrying out adsorption, getting the most appropriate isotherm model is important for predicting the adsorption parameters and the adsorbent system. This study aims to obtain an adsorption isotherm model that is the most suitable for the adsorption of crystal violet by cassava peel biosorbent with high accuracy and to obtain a combined model of the adsorption isotherm model that is the most suitable with the mass balance equation to predict removal efficiency. This research was conducted using secondary data using MATLAB as a supporting tool to perform a non-linear regression and Newton-Raphson iteration. In this research, we conclude that Sips model is the most suitable model with qms = 374,3 mg/g and 0,5933 site heterogeneity. For predict adsorbent mass ratio: adsorbate volume minimum ratio but removal efficiency stay at â‰¥ 90%, we obtain a correlation factor: m/V = -1.10-11Co4 + 2.10-8Co3 â€“ 2.10-5Co2 + 0.015Co + 1.2686.